Exposure to dim artificial light at night increases REM sleep and awakenings in humans. (2nd January 2016) - Cho, Chul-Hyun; Lee, Heon-Jeong; Yoon, Ho-Kyoung; Kang, Seung-Gul; Bok, Ki-Nam; Jung, Ki-Young; Kim, Leen; Lee, Eun-Il
ABSTRACT: Exposure to artificial light at night (ALAN) has become increasing common, especially in developed countries. We investigated the effect of dALAN exposure during sleep in healthy young male subjects. A total of 30 healthy young male volunteers from 21 to 29 years old were recruited for the study. They were randomly divided into two groups depending on light intensity (Group A: 5 lux and Group B: 10 lux). After a quality control process, 23 healthy subjects were included in the study (Group A: 11 subjects, Group B: 12 subjects). Subjects underwent an NPSG session with no light (Night 1) followed by an NPSG session randomly assigned to two different dim light conditions (5 or 10 lux, dom λ : 501.4 nm) for a whole night (Night 2). We found significant sleep structural differences between Nights 1 and 2, but no difference between Groups A and B. Exposure to dALAN during sleep was significantly associated with increased wake time after sleep onset (WASO; F = 7.273, p = 0.014), increased Stage N1 ( F = 4.524, p = 0.045), decreased Stage N2 ( F = 9.49, p = 0.006), increased Stage R ( F = 6.698, p = 0.017) and non-significantly decreased REM density ( F = 4.102, p = 0.056). We found that dALAN during sleep affects sleep structure. Exposure to dALAN during sleep increases the frequency of arousals, amount of shallow sleep and amount of REM sleep. This suggests adverse effects of dALAN during sleep on sleep quality and suggests the need to avoid exposure to dALAN during sleep.